Questões sobre direitos sexuais e direito ao exercício da orientação sexual no contexto dos direitos difusos e coletivos - Silva, José Alessandro Alves da (2008)
The starting point of this summary report is the main focus that sexuality is an inherent part of the human condition, a fundamental right that accompanies humans throughout their entire existence, being a natural, undeniable and unprescriptible right. There are no human beings that could fulfill their life without having the right to exercise sexual freedom, independently of their personal sexual orientation. There is a direct connection between protecting human beings and their sexual orientation. It is essential to remember that the Federal Constitution not only prohibities illegal invasion of the personal hemisphere, but also establishes a positive promotion to exercise it with freedom. The vanguardism of the diffused and collective rights (the private and collective rights) can not perhaps due to the legal traditionalism, be limited to the issues already "codified", such as, consumer, children and adolescents, environment and more recently the disabled ones. Other matters also being challenged by groups or associations is to have the legal protection declared by the right of the transindividuals. We can point out, among them, main issues related to this present work: a guarantee to exercise sexual orientation and sexual rights. Through a vast doctrinarian and legal search, objectively would like to show the clear connection that exists between the issues related to sexual rights and the exercise of the gender sexual orientation, bringing concepts, historic and legislative perspectives, national and international, establishing a bridge between those matters of sexual orientation and Diffused Rights